Whole‐exome sequencing implicates DGKH as a risk gene for panic disorder in the Faroese population. Issue 8 (3rd June 2016) - Gregersen, Noomi O.; Lescai, Francesco; Liang, Jieqin; Li, Qibin; Als, Thomas; Buttenschøn, Henriette N.; Hedemand, Anne; Biskopstø, Marjun; Wang, Jun; Wang, August G.; Børglum, Anders D.; Mors, Ole; et al.
Abstract : The demographic history of the isolated population of the Faroe Islands may have induced enrichment of variants rarely seen in outbred European populations, including enrichment of risk variants for panic disorder (PD). PD is a common mental disorder, characterized by recurring and unprovoked panic attacks, and genetic factors have been estimated to explain around 40% of the risk. In this study the potential enrichment of PD risk variants was explored based on whole‐exome sequencing of 54 patients with PD and 211 control individuals from the Faroese population. No genome‐wide significant associations were found, however several single variants and genes showed strong association with PD, where DGKH was found to be the strongest PD associated gene. Interestingly DGKH has previously demonstrated genome‐wide significant association with bipolar disorder as well as evidence of association to other mental disorders. Additionally, we found an enrichment of PD risk variants in the Faroese population; variants with otherwise low frequency in more outbreed European populations. © 2016 Wiley Periodicals, Inc.